Cutaneous myofibroblastic fibrosarcoma in a margay (Leopardus wiedii): a case report - Bermúdez-Salas, Raúl; Campos, Natalia; Barrantes, Daniel; Arguedas, Randall; Alfaro-Alarcón, Alejandro (Brazilian Journal of Veterinary Pathology, 2020)
A routine check-up was performed on a captive 14-year-old female margay (Leopardus wiedii), a cutaneous mass was detected on the ventral thorax. The mass was surgically removed and sent for histopathological analysis. Histologically, the mass was a poorly-demarcated, highly cellular, infiltrative and unencapsulated mesenchymal neoplasm. Immunohistochemical labeling for smooth muscle actin and vimentin were positive, while desmin and cytokeratin were negative which is consistent with a myofibroblastic fibrosarcoma. This type of tumor has been diagnosed in wild felines, however this seems to be the first report of its occurrence in this L. wiedii. Wildlife oncology studies should be performed to promote our understanding of cancer in a species.